12.1 NON-AUTOCLAVED AERATED CONCRETE WITH IMPROVED PERFORMANCE USING COMPLEX MINERAL AND ORGANOSILICON ADDITIVES - Erdanov Nodirbek Ibragimovich, Abduqayumov Farrux Otabek o’g’li (Innovative technologies in construction Scientific Journal, 2025)
This article presents the development results of non-autoclaved aerated concrete (NAAC) with enhanced performance properties. To improve water resistance and durability, an organosilicon water repellent was combined with mineral additives. Partial substitution of quartz sand with ground river sand, along with the incorporation of microsilica, helped optimize the aggregate particle size distribution and boost strength characteristics. A novel NAAC composition with a density of 500–550 kg/m³ and compressive strength of 4.8–5.0 MPa, not previously reported in the literature, is introduced. The article also includes comprehensive test results covering frost resistance, water absorption, and microstructural analysis.